Correlation of microstructure with cavitation erosion behaviour of a nickel-aluminum bronze in simulated seawater. (August 2019) - Zhang, L.M.; Ma, A.L.; Yu, H.; Umoh, A.J.; Zheng, Y.G.
Abstract: The correlation of microstructure with cavitation erosion (CE) behaviour of Ni-Al bronze in simulated seawater has been clarified. It is found that there exist a large number of dislocations and deformation twins in the α-phases after CE damage, and these dislocations and deformation twins can prevent the fatigue cracks from nucleating and expansion, thereby making Ni-Al bronze a superior CE resistance. Meanwhile, the small size of the α-phases improves the critical shear stress of dislocation movement, thus displaying good strengthening effect on this material. In addition, the microstructure evolution of Ni-Al bronze with different CE time as well as the synergistic effect between CE and corrosion in simulated seawater have also been studied. Highlights: CE induced the high density dislocations and deformation twins in the α-phases. Uniformly distributed κIV phases hindered cracks growth in the vertical direction. The small α-phases improved the critical shear stress of dislocation movement. Synergistic effect between CE and corrosion played a vital role in CE damage.